Mapping The Islam Nusantara Discourse: Bibliometric analysis of conceptual structure and key debates - Nurul Alma Ashofi; Rully Khairul Anwar (UIN Maulana Malik Ibrahim Malang, 2026)
This study was motivated by the rapid development of the discourse on Islam Nusantara in academic literature, contrasted with limited efforts to systematically map its intellectual structure and conceptual debate patterns. The purpose of this study is to map the intellectual structure of Islam Nusantara studies, identify its theoretical foundations, and reveal the primary directions of conceptual debates that have developed in scientific literature. Using a bibliometric analysis method, this study examines 1,653 articles indexed by Scopus between 2017 and 2024, analyzed via the Bibliometrix tool through Biblioshiny. The results show that publications on Islam Nusantara have experienced significant annual growth. The thematic map reveals that the main discourse of Islam Nusantara centers on the relationship between Islam, human values, and religion as a social practice, while themes of Islamism, Islamic law, and nationality occupy an emerging or declining position. Furthermore, keyword network analysis demonstrates a strong connection between the religious, social, and political dimensions within the study of Islam Nusantara. This study concludes that Islam Nusantara in contemporary scientific literature is constructed primarily as a humanistic, moderate, and contextual discourse on Islam, rather than solely as an ideological-political project, and remains open to the development of more specific micro and thematic studies. Future research should explore digital Islam Nusantara, gender, youth, and pesantren globalization. Applying longitudinal bibliometrics and regional comparisons will enhance the field's theoretical depth, empirical richness, and global relevance.Penelitian ini dilatarbelakangi oleh pesatnya perkembangan wacana Islam Nusantara dalam literatur akademik, yang kontras dengan masih terbatasnya upaya untuk memetakan struktur intelektual dan pola perdebatan konseptualnya secara sistematis. Tujuan dari penelitian ini adalah untuk memetakan struktur intelektual studi Islam Nusantara, mengidentifikasi landasan teoretisnya, serta mengungkap arah utama perdebatan konseptual yang berkembang dalam literatur ilmiah. Dengan menggunakan metode analisis bibliometrik, penelitian ini memeriksa 1.653 artikel terindeks Scopus antara tahun 2017 dan 2024, yang dianalisis menggunakan alat Bibliometrix melalui Biblioshiny. Hasil penelitian menunjukkan bahwa publikasi tentang Islam Nusantara mengalami pertumbuhan tahunan yang signifikan. Peta tematik mengungkapkan bahwa wacana utama Islam Nusantara berpusat pada hubungan antara Islam, nilai-nilai kemanusiaan, dan agama sebagai praktik sosial, sementara tema Islamisme, hukum Islam, dan kebangsaan berada pada posisi yang baru muncul (emerging) atau menurun (declining). Lebih lanjut, analisis jaringan kata kunci menunjukkan hubungan yang kuat antara dimensi keagamaan, sosial, dan politik dalam studi Islam Nusantara. Penelitian ini menyimpulkan bahwa Islam Nusantara dalam literatur ilmiah kontemporer dikonstruksikan secara utama sebagai wacana Islam yang humanis, moderat, dan kontekstual, bukan semata-mata sebagai proyek ideologis-politik, serta tetap terbuka bagi pengembangan studi mikro dan tematik yang lebih spesifik. Penelitian masa depan harus mengeksplorasi Islam Nusantara digital, gender, pemuda, dan globalisasi pesantren. Penerapan bibliometrik longitudinal dan perbandingan regional akan meningkatkan kedalaman teoretis, kekayaan empiris, dan relevansi global dari bidang ini.